Analysis of Starlink System Service Capabilities - WANG Jingxian; YU Zhigang; ZHU Chao; SUN Jiazheng; LEI Jing (天地一体化信息网络)
This paper first provided an overview of the current status of the Starlink constellation development, then studied the Starlink system from aspects such as system composition, satellite iteration versions, constellation configuration, and system development characteristics. Finally, through simulation, a comparison of end-to-end transmission latency based on the Starlink constellation and terrestrial fiber optics was made, and the the relationship between the end-to-end transmission distance and the delay under different transmission paths was obtained. Moreover, through link estimation, the service level of Starlink satellites for different services could be evaluated from the perspective of transmission rate. Further, an analysis of the coverage capabilities of a single satellite and the constellation was conducted.